HUMAN TRAFFICKING AND WAR IN UKRAINE: RESILIENCE IN EXPLORING STUDENT RESPONSE - Paliichuk, Elina (The Modern Higher Education Review, 2023)
This paper meets challenges in exploring the problems of human trafficking awareness among Ukrainian youth under war conditions. The mission of this social and pedagogical linguistic initiative has been reconsidered in the framework of the CEFRES fellowship, given the general and specific pre-conditions of vulnerability to human trafficking among Ukrainian youth. The paper highlights physical, psychological, technical, and pedagogical difficulties and offers solutions for resilient research. Attention is drawn to adjusting the methods under limitations such as a reduced sample of volunteering respondents and measuring the war impact. The solutions include accumulating empirical data for significant measurements for two academic years and upcoming surveying possibilities regarding the “war vs. no war” factors. Other outcomes of tackling impediments imply the possibility of retaining students’ attention to human trafficking under war conditions through immersive experiences and reflexive activities with simultaneous collecting empirical data, introducing the awareness activities into the e-course (Moodle), and encouraging students to explore cases and evaluate the message. These solutions can help filter the significant results under four parameters of the CEFRES-supported project such as metaphor, storytelling, schemata, and sensory language for registering effective ways of immersive learning experiences.